(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Accidents happen without being predicted by the victim, in everyday life Accidents can happen anywhere, at school, at home, road, at work, or in other places. The consequences caused by it include minor, moderate, and severe injuries, and even death. Several factors that affect the consequences of accidents experienced by victims include : severity of the injury, the time between events to First Aid In Accidents services, First Aid In Accidents, skills of First Aid In Accidents officers, mileage to the hospital, availability of transportation to the hospital and communication to the destination hospital. Risk factors for accidents at school include injuries, bleeding, sprains, hazards posed during learning such as sports or when students play in the yard, and ergonomic hazards from moving things or objects. Accuracy and speed in providing first aid in schools against injuries and medical emergencies will help reduce complications, medical expenses, and death. The knowledge and attitude of the helper will affect the speed and accuracy in carrying out help. The subjects of this activity were 23 students of SMAIT Almumtaz Pontianak City. Activities carried out in February-April 2022 include the stage of assessing each student’s knowledge, after which it conducts material provision and reassessment of students’ knowledge about first aid in accidents. Participants enthusiastically participated in counseling about First Aid In Accidents in schools. The results of the activity showed an increase in knowledge in the participants’ average knowledge before health education score of 78.5% while after being given health education the average knowledge score was 91%, there was an increase of 12.5% in student knowledge related to First Aid In Accidents in schools. Keywords: First aid in accidents, Knowledge, Students